"Call for Help Immediately": A Discourse Analysis of Resident Assistants' Responses to Sexual Assault Disclosures. (September 2020) - Holland, Kathryn J.; Bedera, Nicole
Formal support providers can play a critical role in sexual assault survivors' well-being (e.g., providing resource referrals). In a university setting, resident assistants (RAs) are key support providers with a unique relationship to survivors based on their dual roles as help-provider and peer. We examined 305 RAs' responses to student sexual assault disclosure scenarios. Employing a critical discourse analysis, we identified four discourses used by RAs in their discussion of resources: controlling, gatekeeping, minimizing, and empowering. Due to power dynamics between RAs and residents, we conclude that empowering discourses would facilitate survivors' access to other resources (e.g., sexual assault center).